Pre-clinical and Clinical Implications of “Inside-Out” vs. “Outside-In” Paradigms in Multiple Sclerosis Etiopathogenesis - Titus, Haley E.; Chen, Yanan; Podojil, Joseph R.; Robinson, Andrew P.; Balabanov, Roumen; Popko, Brian; Miller, Stephen D. (Frontiers in Cellular Neuroscience, 2020)
Multiple Sclerosis (MS) is an immune-mediated neurological disorder, characterized by central nervous system (CNS) inflammation, oligodendrocyte loss, demyelination and axonal degeneration. Although autoimmunity, inflammatory demyelination and neurodegeneration underlie MS, the initiating event has yet to be clarified. Effective disease modifying therapies need to both regulate the immune system and promote restoration of neuronal function, including remyelination. The challenge in developing an effective long-lived therapy for MS requires that three disease-associated targets be addressed: (1) self-tolerance must be re-established to specifically inhibit the underlying myelin-directed autoimmune pathogenic mechanisms; (2) neurons must be protected from inflammatory injury and degeneration; (3) myelin repair must be engendered by stimulating oligodendrocyte progenitors to remyelinate CNS neuronal axons. The combined use of chronic and relapsing remitting experimental autoimmune encephalomyelitis (C-EAE, R-EAE) (“outside-in”) as well as progressive diphtheria toxin A chain (DTA) and cuprizone autoimmune encephalitis (CAE) (“inside-out”) mouse models allow for the investigation and specific targeting of all three of these MS-associated disease parameters. The “outside-in” EAE models initiated by myelin-specific autoreactive CD4+ T cells allow for the evaluation of both myelin-specific tolerance in the absence or presence of neuroprotective or remyelinating agents. The “inside-out” mouse models of secondary inflammatory demyelination are triggered by toxin-induced oligodendrocyte loss or subtle myelin damage, which allows evaluation of novel therapeutics that could promote remyelination and neuroprotection in the CNS. Overall, utilizing these complementary pre-clinical MS models will open new avenues for developing therapeutic interventions, tackling MS from the “outside-in” and/or “inside-out”.